Optimization of the Natural Disaster Mitigation Website (Gancana) as a Medium for Disaster Mitigation Socialization to Improve Preparedness of the Aceh Community - Muhammad Kautsar; Farouq Ahmed Ashim (International Journal of Scientific Research, 2024)
This study aims to evaluate the effectiveness of the "GANCANA" website platform in disseminating information and education on disaster mitigation to the Aceh community and to identify barriers in empowering the community through this platform. The research method used is descriptive qualitative, providing a comprehensive overview of the use of the "GANCANA" website as a medium for disaster mitigation socialization in Aceh. Data were collected through literature review and direct observation of the characteristics of the "GANCANA" website and how the Aceh community accesses and utilizes it. The results of the study show that the use of information technology in disaster mitigation has been previously identified, but this research emphasizes the use of the "GANCANA" website in Aceh. The importance of integrated disaster risk communication in disaster management is also highlighted, as well as the role of socialization in shaping the understanding and behavior of the community in facing disasters. Disaster mitigation is carried out through both structural and non-structural approaches, including physical infrastructure development and socialization approaches. This study contributes to understanding the optimization of the "GANCANA" website as a tool for disaster mitigation socialization in Aceh.